Supercomputing's Exaflop Target. (Communications of the ACM, 2011)
The article discusses the challenges of energy consumption and parallelism to the progress of supercomputers. The author offers brief information on the rankings of several of the world's supercomputers, such as Japan's K computer, China's Tianhe-1A computer, and the U.S.'s Jaguar computer, noting that various national governments are reconsidering the value of supercomputer ratings. He further notes that computer scientists are also skeptical about the value of the ratings and that measuring petaflops, which are the number of floating-point operations per second, is not useful work. A comparison of central processing units (CPUs) versus central processing unit/graphics processing unit (CPU/GPU) hybrids is presented.